(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2019)
The Software Defined Networking (SDN) is an emerging network architecture where network control is decoupled from forwarding and is directly programmable. The explosion of mobile devices and content, server virtualization and advent of cloud services are among the trends driving the networking industry to reexamine traditional network architectures. Many conventional networks are hierarchical, built with tiers of Ethernet switches arranged in a tree structure. This design made sense when client-server computing was dominant, but such a static architecture is all suited to the dynamic computing and storage needs of today’s enterprise data centers, campuses and carrier environments. Some of the key computing trends driving the need for a new network paradigm include: challenging traffic patterns, consumarization of IT, rise of cloud services and big data transactions